2017
DOI: 10.18203/2349-3291.ijcp20175506
|View full text |Cite
|
Sign up to set email alerts
|

Effect of probiotics on constipation in children

Abstract: Background: Constipation in children is a common problem. A constipated child has infrequent bowel movements or hard, dry stools. This is a randomized controlled trial to find the relationship between probiotics and constipation in children. Methods: This study was a randomized, controlled blinded trial conducted in Department of Paediatric. This was done during a period of January 2014 to January 2016 conducted in 50 patients. The patients were divided into two groups randomly namely group A who received lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 3 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…216 Santhosh Jose evaluated the effects of probiotics consumption on the treatment of constipation and exhibited the desirable effects of probiotics in this condition. 217 In another study reported by Choi et al, significant reduction of Bifidobacterium and Bacteroides species in the feces of the patients suffering from functional constipation was observed. 218 Dimidi et al exhibited that probiotics, particularly B. lactis, improved stool consistency, stool frequency and whole gut transit time.…”
Section: Constipationmentioning
confidence: 88%
“…216 Santhosh Jose evaluated the effects of probiotics consumption on the treatment of constipation and exhibited the desirable effects of probiotics in this condition. 217 In another study reported by Choi et al, significant reduction of Bifidobacterium and Bacteroides species in the feces of the patients suffering from functional constipation was observed. 218 Dimidi et al exhibited that probiotics, particularly B. lactis, improved stool consistency, stool frequency and whole gut transit time.…”
Section: Constipationmentioning
confidence: 88%
“…According to our recent search and the last review of Rodriguez's study [19] on pediatric functional constipation in 2021, some researchers, including Russo et al, Jose et al, Guerra et al, and Sadeghzadeh et al found the positive effect of probiotics on pediatric functional constipation [24][25][26][27]. Some other investigations have shown the usefulness of specific strains of probiotics for the treatment of pediatric functional constipation [28][29][30].…”
Section: Outcomes and Estimationmentioning
confidence: 98%